Determinants of Corporate Governance on Capital Expenditure Allocation Efficiency and Long-Term Financial Performance Optimization - Tristanti , Rany Fatima; Tasya, Sarvana Al (CV. HEI PUBLISHING INDONESIA, 2025)
This research investigates how corporate governance determinants influence capital expenditure (Capex) allocation efficiency and long-term financial performance. Addressing the core agency conflict, the study explores whether robust oversight mechanisms can prevent suboptimal investment decisions. Using secondary data from 248 non-financial firms listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period and official reports published by the Financial Services Authority (OJK), investment efficiency was measured using a growth-based residual model. The findings indicate that board independence and audit committee meeting frequency significantly mitigate capital waste, while excessive managerial power exacerbates investment inefficiency. Furthermore, statistical analysis reveals that efficient Capex allocation is a primary driver of Return on Invested Capital (ROIC), explaining 24.5% of its variance. This study contributes to agency and corporate governance literature by empirically demonstrating the mediating role of capital expenditure efficiency in linking governance mechanisms and long-term financial performance within an emerging market context. The results highlight that strengthening board oversight is essential for ensuring strategic investment discipline and optimizing corporate financial sustainability.